Automated Recording of RNA Differential Display Patterns from Pig Granulosa Cells. (January 1998) - Motlik, J.; Carnwath, J.W.; Herrmann, D.; Terletski, V.; Anger, M.; Niemann, H.
We have developed a protocol for fast, nonradioactive, mRNA differential display reverse transcription PCR (DDRT-PCR) based on a commerical automated sequencer with RNA isolated from pig granulosa cells. We sought to discover conditions that would minimize the problem of using relatively small primers labeled with large infrared dye molecule, IR41, required for the sequencer. Extended IR41-labeled primers IR41-AAGC-T11 -A, IR41-AAGC-T11 -C and IR41-AAGC-T11 -G gave more consistent differential display patterns than shorter anchored primers (IR41-T11 A, IR41-T11 C and IR41-T11 G) without the additional (AAGC) cloning site. The optimal concentration of the extended labeled (downstream) primers was 20 pmol when 13-mer arbitrary (upstream) primers were used at a concentration of 4 pmol. Background smear and the intensity of amplified bands was significantly improved by changing from conventional Taq DNA polymerase to AmpliTaq ® Gold™ polymerase, which permits an improved "hot start" for the reaction. Running time (during which a digitized gel image is recorded) for a 26-cm polyacrylamide gel was 4 h, enabling us to analyze 90 reactions in an 8-h day. This protocol offers a rapid and reliable nonradioactive method for comparing gene expression patterns for various research or diagnostic purposes.